Design, synthesis, and antiproliferative activity evaluation of novel cyclic secondary amine containing dithiocarbamate derivatives as potent EGFR inhibitors - Uslu, Harun; Osmaniye, Derya; Oncu, Elif; Guven, Merve; Ozkay, Yusuf; Kaplancikli, Zafer Asim (Elsevier, 2025)
The EGFR inhibition treatment option, discovered due to in-depth research into the existence of a wide variety of cancer diseases and their treatment, has opened a new path in drug design and development. This study designed and synthesized 10 new cyclic secondary amine derivatives containing dithiocarbamate as EGFR inhibitors for cancer treatment. Moreover, it is derivatized with benzoxazinone or benzothiazonone rings. The structures of the newly synthesized compounds were elucidated by 1H NMR, 13C NMR, and HRMS spectroscopic methods. MTT analyses were performed to determine the antiproliferative activity of all synthesized compounds (2a-j). All synthesized compounds and Doxorubicin used as a reference drug, were tested against A549 and NIH3T3 cell lines. Compounds 2f and 2g, which gave the best results against the cell lines, were compared with erlotinib, an EGFR inhibitor, for EGFR tyrosine kinase inhibition. The IC50 value of the compound 2f with the best result was found to be 0.079 +/- 0.002 mu M, while the IC50 value of the reference drug Erlotinib was found to be 0.003 +/- 0.001 mu M. As a result of molecular docking studies, it was observed that compounds 2f and 2g had the best poses on the active site of EGFR (PDB ID: 4HJO) and interacted with amino acids important for activity. After in vitro and in silico studies evaluations of the designed and synthesized compounds, it was revealed that compounds 2f and 2g were promising compounds in future advanced EGFR inhibition research studies. Among the benzothiazinone and benzoxazinone derivatives carrying the same groups, benzothiazinone derivatives were found to have higher EGFR inhibitory effects.
Keywords: Antiproliferative; Dithiocarbamate; Cyclic secondary amine; EGFR; Molecular docking